Forming-Free TaOx Based RRAM Device with Low Operating Voltage and High On/Off Characteristics. (1st January 2015) - Jiang, Y.; Tan, C. C.; Li, M. H.; Fang, Z.; Weng, B. B.; He, W.; Zhuo, V. Y.-Q.
Abstract : A forming-free TaOx based RRAM cell is demonstrated with low operation voltage and large resistance window. RRAM devices with Pt/TaOx /TiN and Pt/TaOx /Ta film-stacks are investigated in this work. For devices with TiN as top electrode (TE), the initial resistance is at OFF state, thus a forming process is needed prior to subsequent switching operations. For devices with Ta as TE, the initial resistance is at ON state, negating the need for a forming process. This is attributed to the dielectric thinning effect caused by the interfacial reaction between the TaOx and Ta layers during forming gas anneal process. In addition, with Ta as TE, smaller | VSET | and | VRESET | and wider OFF/ON ratio window are observed. Thermal stability up to 400°C during post deposition annealing process with N2 and O2 are studied in this work, electrical results suggested excellent thermal stability for this TaOx based RRAM devices.